PERSEPSI SISWA SEKOLAH DASAR TERHADAP KONSEP BELAJAR SETELAH MENONTON FILM JUMBO - Diva Ghefira Rahmadani; Hendri Purbo Waseso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to analyze elementary school students' perceptions of the concept of learning after watching the film "Jumbo" and to identify the learning values understood by students through the viewing experience. The approach used is descriptive qualitative with a phenomenological method. The subjects of this study are three fourth-grade students from MI Ma’arif Nu Banteran Sumbang, selected through purposive sampling techniques. Data were collected through in-depth interviews and analyzed using the steps outlined by Miles and Huberman, which include data reduction, data presentation, and conclusion drawing. The results indicate that the film "Jumbo" has a varied impact on students' learning perceptions. The majority experienced a shift in their learning perception towards a more enjoyable experience, while other informants showed stable perceptions without significant changes. Additionally, students were able to understand the values of perseverance, courage, and teamwork from the film's scenes and relate them to their own learning experiences. Overall, the research emphasizes that the film "Jumbo" can have a constructive impact on students' learning perceptions through character identification and the interpretation of character values. These findings imply that teachers should optimize the use of films as a medium for character education and motivation in elementary schools.